Evaluation of reference-crop evapo-transpiration by empirical method for predicting consumptive water use of a crop in a tropical wet-and-dry climate - BELLOW, N J (The Indian Journal of Agricultural Sciences, 2013)
Reference-crop evapo-transprration (ETo) was determined according to 4 empirical methods using climatic data for the different phenological stages ofmaize (Zea mays L.) grown during the rainy seasons of 1992-95. Evaluation of the empirical methods for the prediction of crop-consumptive water use (ETcrop) was based on the variability of derived ETo estimates and the capability of each estimate to reliably predict the (ETcrop) during the different phenological stages of growth. The modified Penman method effered the best result with significant (P = 0.01) coefficient of determination of (ETcrop. Next to Penman is the modified pan-evauoration method. The modified radiation method was graded next and lastly the moditied Blaney-Criddle approach. The relative reliability of each method in terms of accuracy of both measured and extrapolated meteorological data utilized is also discussed.